POTENSI PENINGKATAN PEMBERDAYAAN WAKAF DI KABUPATEN TANAH DATAR - ELIMARTATI, ELIMARTATI (State Institute for Islamic Studies Batusangkar, 2016)
The study analyzes the potential, opportunities, human resources and challenges in improving wakaf empowerment in Tanah Datar. The method that used in this research is a field research. To collect data that needed in this study is by interviews and documentation. Data was analyzed by descriptive qualitative. Result of this study is expected to produce guidelines or rule for the conduct of wakaf and can be used as a foothold in making policies. Base on data, potential of wakaf in in Tanah Datar about 639 locations already have wakaf certificate (AIW). A religious community of Tanah Datar people could be more efective to improve wakaf empowerment by using the rule that stated by government to manage of wakaf in Tanah Datar. And this rule also To avoid any mistake or human error in mangement to empower of wakaf. Keywords: Wakaf, Potential, Empowerment.